Women's Empowerment through Gender-Based Academic Writing: A Participatory Action Research Study of Kohati Babel Raya (Empower : Jurnal Pengembangan Masyarakat Islam, 2026)
Women continue to experience limited social space and the persistence of patriarchal dominance in various aspects of life. These conditions highlight the need for empowerment initiatives that promote independence and critical awareness among women. Korps HMI-Wati (KOHATI) Babel Raya, as a semi-autonomous body of Himpunan Mahasiswa Islam (HMI), plays a strategic role in strengthening women’s intellectual capacity through literacy initiatives and gender-based writing training. Empowering women through writing activities positions them not only as recipients of knowledge but also as producers of knowledge and agents of social change. This community service program aims to empower women through gender-based scientific and non-scientific writing activities within KOHATI Babel Raya. The study employs a qualitative approach based on Participatory Action Research (PAR), emphasizing active participation and collaboration between researchers and participants throughout the empowerment process. The mentoring activities include literacy-strengthening, writing workshops, and guided practice in producing written work. The results indicate that writing can serve as an effective medium for women’s empowerment. The program successfully enhanced participants’ awareness of gender issues and their writing skills. As an output, participants produced a non-scientific publication, a gender-based short-story anthology authored by KOHATI Babel Raya members, which has been published with an ISBN.